FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN IMUNISASI DASAR PADA ANAK DI DESA DAMULI KEBUN KECAMATAN KUALUH SELATAN KABUPATEN LABUHANBATU UTARA TAHUN 2024 - Rohimah (Akupun Tour Publisher, 2024)
Background: Immunization is a healthcare service aimed at protecting individuals from vaccinepreventable diseases (VPDs). In North Labuhanbatu Regency, the coverage of complete basic immunization (IDL) is 83.7%, with 6,902 children having received IDL, while 336 children have not yet received it. This coverage has not yet met the target of 99%, highlighting the need for continuous efforts to accelerate the achievement of the IDL programs targets. Purpose: This study aims to identify the factors associated with the completeness of basic immunization among children in Damuli Kebun Village, Kualuh Selatan District, North Labuhan batu Regency in 2024. Method: The study uses a quantitaive research method with a cross-sectional design, conducted from January to August 202. The sample consist of 46 mothers with children aged 13-24 months. Results: The results show a relationship between maternal attitudes, income, education level, and knowledge with the completeness of immunization in Damuli Kebun Village, Kualuh Selatan District, North Labuhanbatu Regency. Disscusion and Conclusion: It is recommended that mothers of young children actively seek information about the importance of immunization and adhere to the complete immunization schedule. Additionally, health center heads are encouraged to strengthen the role of healthcare workes in educating the public about the importance of complete immunization.